The The Relationship Between Physical Fitness and Shooting Ability of Students Interested in Football Sports Talents - Putra, Dio Firmansyah; Subekti, Nur; Indarto, Pungki (Universitas PGRI Palembang, 2025)
Students of the UMS Physical Education Talent Interest have several problems, namely the different levels of physical fitness of students, which can be seen when playing or practicing, causing inconsistent performance and decreased focus and concentration, which can increase the risk of injury. In addition, students are still less aware of the importance of physical fitness to playing skills, including muscle strength, which can affect their shooting ability. This condition often becomes an obstacle in improving overall game performance. This study aims to determine the relationship between physical fitness and the shooting ability of UMS Physical Education Football MBO students. This study uses a quantitative method with a correlational design to measure the degree or relationship between two or more variables, while data is collected using measurements. The sample in this study were active UMS Physical Education Football MBO students totaling 35 students. This study uses